2017
DOI: 10.1136/bcr-2017-221438
|View full text |Cite
|
Sign up to set email alerts
|

Constrictive bronchiolitis presenting with a mixed obstructive and restrictive pattern, associated with acid reflux

Abstract: A previously healthy 55-year-old woman presented with worsening dyspnoea on exertion. The patient lived at altitude, did not smoke and had no exposure to occupational or environmental toxins. Her physical examination, including pulmonary, was unremarkable. Pulmonary function tests showed forced expiratory volume in 1 s/forced vital capacity ratio 74% predicted, diffusing capacity for carbon monoxide (DLCO) 92% predicted and residual volume 213% predicted. Rheumatological workup was negative. Chest radiograph s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Several studies have described the association of gastro-esophageal reflux disease (GERD) and BOS after lung transplantation ( 8 , 9 ). Capel et al reported a case of a non- transplant OB patient with a large volume of gastro-esophageal reflux and considered GERD to be associated with the development of OB ( 10 ). They also suggested that GERD might account for some of the cases of idiopathic OB.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described the association of gastro-esophageal reflux disease (GERD) and BOS after lung transplantation ( 8 , 9 ). Capel et al reported a case of a non- transplant OB patient with a large volume of gastro-esophageal reflux and considered GERD to be associated with the development of OB ( 10 ). They also suggested that GERD might account for some of the cases of idiopathic OB.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the BAL fluid profiles in dogs with sHH and GERD warrant additional investigation because GERD has been implicated in the pathogenesis and progression of respiratory diseases such as asthma, bronchiolitis, interstitial pulmonary fibrosis, and chronic obstructive pulmonary disease in people. [37][38][39][40] Unfortunately, underutilization of BAL fluid in dogs in our study precluded evaluation of the effect of GERD on BAL fluid cytology in dogs.…”
Section: T a B L E 5 Summary Of Recognized Aerodigestive Diseases In ...mentioning
confidence: 99%